2004
DOI: 10.4049/jimmunol.173.12.7230
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin Elicits Cytokine Release in Murine Th2-Type T Cell Clone D10.G4.1

Abstract: Neuromedin U (NmU), originally isolated from porcine spinal cord and later from other species, is a novel peptide that potently contracts smooth muscle. NmU interacts with two G protein-coupled receptors designated as NmU-1R and NmU-2R. This study demonstrates a potential proinflammatory role for NmU. In a mouse Th2 cell line (D10.G4.1), a single class of high affinity saturable binding sites for 125I-labeled NmU (KD 364 pM and Bmax 1114 fmol/mg protein) was identified, and mRNA encoding NmU-1R, but not NmU-2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…This is consistent with the evidence that tumor-microenvironment Neuromedin U enhances lung metastasis Y Wu et al interactions affect local cancer growth, invasion and metastasis (Chung et al, 2005). NMU can also induce the release of inflammatory cytokines in T helper-2 (Th2)-type T cells, mast cells or macrophages (Johnson et al, 2004;Moriyama et al, 2005Moriyama et al, , 2006. These cytokine-releasing immune cells may stimulate neovascularization to promote the growth of neoplasms in humans.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the evidence that tumor-microenvironment Neuromedin U enhances lung metastasis Y Wu et al interactions affect local cancer growth, invasion and metastasis (Chung et al, 2005). NMU can also induce the release of inflammatory cytokines in T helper-2 (Th2)-type T cells, mast cells or macrophages (Johnson et al, 2004;Moriyama et al, 2005Moriyama et al, , 2006. These cytokine-releasing immune cells may stimulate neovascularization to promote the growth of neoplasms in humans.…”
Section: Discussionsupporting
confidence: 87%
“…NMU itself has an anorexigenic effect in animals (Howard et al, 2000;Hanada et al, 2004;Shousha et al, 2006), and transgenic overexpression of it promotes leanness in mice (Kowalski et al, 2005). As NMU can function as a proinflammatory mediator by promoting interleukin (IL)-6 production in Th2-type T cells or macrophages (Johnson et al, 2004;Moriyama et al, 2006) and inhibition of IL-6 can partially attenuate or reverse cancer cachexia (Strassmann and Kambayashi, 1995), this might be a mechanism underlying NMU-mediated cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, c-Met also appears to be upregulated following NmU treatment, suggesting a positive loop between these 2 molecules (131 ). Regarding other genes that are regulated by NmU, this peptide appears to be required for secretion of IL-6, a cytokine involved in cancer cell growth and cachexia (124 ), although it is not clear whether NmU affects IL-6 mRNA concentrations (123,135 ). NmU was also found to positively regulate Forkhead box protein M1 (FOXM1), a transcription factor and human protooncogene (45 ).…”
Section: Cancermentioning
confidence: 99%
“…NmU was first shown to induce synthesis and release of several different cytokines [interleukin-4 (IL-4), IL-5, IL-6, IL-10, and IL-13) from a mouse T-helper 2 cell line in an NMUR1-dependent fashion (123 ). It was later shown that NmU is required for IL-6 production, as shown by impaired IL-6 secretion by macrophages in NmU ÏȘ/ÏȘ mice (124,125 ).…”
Section: Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation